Pengaruh Motivasi, Efikasi Diri (Self Efficacy), Beban Kerja dan Keterampilan (Skill) Menulis terhadap Produktivitas Buku Ajar Dosen yang Diterbitkan (Studi di Universitas Brawijaya Malang) - Margono, Margono; Atma, Aan Widhi (Jurnal Aplikasi Manajemen, 2008)
The purpose of this study was to determine the variables that explain the text book productivity academic staff in Brawijaya University. In this study, publication in books were used as a surrogate for research productivity. The study described the text book productivity of Barawijaya University, their motivation to write a book, their self efficacy, workload activity and skill of writing. Study findings suggest that: (a) text book productivity is a significantly relationship with motivation, skill of writing and workload activity; (b) there is no relationship between text book productivity and self efficacy. This study's population was defined as lecturer that write a text book in five years later (2002-2007). The sample size comprised of 32 academic staff drawn from population. Data collection was carried out using snowball sampling technique. The data obtained were treated statistically using regression analyses. From the regression model showed the F statistic was positive (10,952) and significant at the 0.000 level. This indicated a good fil between the observed data and the models, and the independent variables are related to the dependent variable. The coefficient regression for self efficacy was not significantly different from zero at the 0,05 level (p=0,3200. The regression standardized coefficient for the workload activity was negative (-.764) and significant at the 0,000 level. In fact the beta coefficient for workload activity was the highest, indicating this was the most important variable in the model.